Sustainable development using integrated energy systems and solar, biomass, wind, and wave technology - Østergaard, Poul Alberg; Duic, Neven; Kalogirou, Soteris A. (My University, 2024)
This articles reviews some of the latest trends within renewable energy sources based on biomass, solar, wind and wave technologies as well as integrated renewable energy-based systems. The review takes a starting point in work presented at the Sustainable Development of Energy, Water and Environmental Systems (SDEWES) 2023 conference and relates the findings of the presented work to previous research findings within the field. While general pathways for the energy transition are already well established, this article shows that there are still open questions for the more specific choices to be made in the transition process.
Keywords: Biomass in the energy transition; Integrated energy systems; Solar technologies; Wave power resources; Wind power resources